THE DEVELOPMENT AND METHODOLOGY OF ILM AL-MUNASABAT AL-QUR’ANIYA “THE SCIENCE OF INTERRALATIONS BETWEEN QUR’ANIC VERSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the formation and theoretical foundations of “Ilm al-Munasabat al-Qur’aniya the science that studies the internal verbal and semantic interconnections among the verses of the Qur’an. The research analyses the linguistic and terminological interpretations of this science and its concepts, its historical development and role within modern tafseer methodology. Drawing on the works of exegetes such as al Baqai al - Suyuti and al Razi, the study reveals the essence of various types of relationships between verses, including tanasub (correspondence), tadadd (contrast), tanzir (analogy), istitrad (digression), uslub al-hakim (the wise style) and intiqal (transition). The article argues that understanding the thematic coherence among Qur’anic verses serves as a key principle in tafsir, ensuring logical consistency, theological clarity and a fuller appreciation of the Qur’an’s miraculous structure ijaz al-nazm. According to the findings, the science of Munasabat al-Qur’an constitutes the theoretical basis for studying the order and composition of the Qur’an and is established as an independent scholarly discipline that ensures the comprehensive integration of Qur’anic exegesis sciences.